Language Impairment and Arachnoid Cysts - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Universite Catholique de Louvain, Brussels, Belgium, and Universite de Sherbrooke, Quebec, Canada studied 2 patients presenting with arachnoid cysts associated with cognitive impairment., particularly language impairment.